Concentrations of the Genotoxic Metals, Chromium and Nickel, in Whales, Tar Balls, Oil Slicks, and Released Oil from the Gulf of Mexico in the Immediate Aftermath of the Deepwater Horizon Oil Crisis: Is Genotoxic Metal Exposure Part of the Deepwater Horizon Legacy? - Wise, John Pierce (American Chemical Society, 2014)
[Image: see text] Concern regarding the Deepwater Horizon oil crisis has largely focused on oil and dispersants while the threat of genotoxic metals in the oil has gone largely overlooked. Genotoxic metals, such as chromium and nickel, damage DNA and bioaccumulate in organisms, resulting in persistent exposures. We found chromium and nickel concentrations ranged from 0.24 to 8.46 ppm in crude oil from the riser, oil from slicks on surface waters and tar balls from Gulf of Mexico beaches. We found nickel concentrations ranged from 1.7 to 94.6 ppm wet weight with a mean of 15.9 ± 3.5 ppm and chromium concentrations ranged from 2.0 to 73.6 ppm wet weight with a mean of 12.8 ± 2.6 ppm in tissue collected from Gulf of Mexico whales in the wake of the crisis. Mean tissue concentrations were significantly higher than those found in whales collected around the world prior to the spill. Given the capacity of these metals to damage DNA, their presence in the oil, and their elevated concentrations in whales, we suggest that metal exposure is an important understudied concern for the Deepwater Horizon oil disaster.